2011
DOI: 10.1097/scs.0b013e31820f7d07
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Jaw Lymphoma in an Iranian Population

Abstract: The epidemiology of different types of oral lymphoma in a sample of Iranian population was not similar with other populations of the world. Immunohistochemistry and molecular methods are required to prove the diagnosis in addition to typing of lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…Gnepp reported that DLBL was the most common type of lymphoma of Waldeyer’s tonsillar ring followed by peripheral T cell lymphoma, MALT (mucosa-associated lymphoid tissue) lymphoma and FL in a decreasing order of prevalence ( 14 ) In our study, MALT and peripheral T cell lymphoma were each seen in one case and follicular type was found in 20 cases. In a study by Mohtasham et al ( 15 ), on 36 cases of oral lymphomas, DLBL (41.1%), low-grade B cell lymphoma (35.2%), peripheral T cell lymphoma (11.7%), Burkitt’s lymphoma (5.8%) and HL (5.8%) had the highest frequency in decreasing order. Although Mohtasham et al ( 15 ) did not use the accredited WHO classification for lymphomas, DLBL was the most common subtype, which is in line with the results of the current study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gnepp reported that DLBL was the most common type of lymphoma of Waldeyer’s tonsillar ring followed by peripheral T cell lymphoma, MALT (mucosa-associated lymphoid tissue) lymphoma and FL in a decreasing order of prevalence ( 14 ) In our study, MALT and peripheral T cell lymphoma were each seen in one case and follicular type was found in 20 cases. In a study by Mohtasham et al ( 15 ), on 36 cases of oral lymphomas, DLBL (41.1%), low-grade B cell lymphoma (35.2%), peripheral T cell lymphoma (11.7%), Burkitt’s lymphoma (5.8%) and HL (5.8%) had the highest frequency in decreasing order. Although Mohtasham et al ( 15 ) did not use the accredited WHO classification for lymphomas, DLBL was the most common subtype, which is in line with the results of the current study.…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Mohtasham et al ( 15 ), on 36 cases of oral lymphomas, DLBL (41.1%), low-grade B cell lymphoma (35.2%), peripheral T cell lymphoma (11.7%), Burkitt’s lymphoma (5.8%) and HL (5.8%) had the highest frequency in decreasing order. Although Mohtasham et al ( 15 ) did not use the accredited WHO classification for lymphomas, DLBL was the most common subtype, which is in line with the results of the current study. In addition, Kemp et al ( 1 ) reported that DLBL comprised 58% and B cell lymphoma comprised 98% of cases.…”
Section: Discussionmentioning
confidence: 97%
“…Usually non-Hodgkin lymphomas of the head and neck area occur more often in men, with approximately 55-77% of cases 12 , 13 , 15 , 16 . In the present study only 45% of all patients were men, so that women were slightly more often affected.…”
Section: Discussionmentioning
confidence: 99%
“…Mashhad has a substantial Turkmen community, which is East Asian in contrast to the mainly Indo-European community in Teheran. The relative period prevalence in Teheran was 0.74 [41], the highest of all case series in Table 1, whereas that of Mashhad was 0.20 [40], almost the lowest of all case series. The difference in the maxilla/mandible ratio between these two case series tended to significant (FET = 0.080).…”
Section: Discussionmentioning
confidence: 99%
“…Ethnicity may also play a role in some of the other outliers observed in Tables 1 and 2. After the Teheran Iranians [41], the Nigerians [35] had the second highest relative period prevalence of 0.60.…”
Section: Discussionmentioning
confidence: 99%